GIS based flood extent assessment using MODIS satellite remote sensing and spatial analysis - Akram, Afshin; Tahir, Arifa; Alam, Asifa (Frontiers in Earth Science, 2024)
Floods are one of the most destructive and common natural disaster as it affects human lives, economy and environment. Pakistan is prone to flooding because it is greatly affected by climate change. Mianwali region, Pakistan was selected as study area because this region is vulnerable to floods and have been affected by major floods in Pakistan in 2010 and no proper study on vulnerability assessment and flood extent mapping has been done in this area. This study evaluates flood extent mapping of Mianwali region by using MODIS and NDWI techniques and to develop a cumulative flood risk map for 10 years (2010-2020). For the Flood Extent Mapping MODIS Product “MODIS Combined 16-Day NDWI” was used. This product is generated from the MODIS/MCD43A4 surface reflectance composites and provides a single NDWI value for 16 daily composite images. (Earth Data Catalogue). The flood extent maps of years 2010 to 2020 were developed. These flood extent maps demonstrated Mianwali villages of high flood risk zones and shallow flood risk zones. Results revealed that the people living in villages named Dhup sari, Sheikhan Wala, Arsala Wala, Moza wala, Allahkhel wala and JanayKhel wala are at a greater risk of experiencing natural disasters as they are located alongside river Indus. In conclusion, Mianwali is at high danger of flooding due to its location and lack of pre-disaster preparedness. The data obtained from this study is critical for emergency response and rehabilitation efforts. The findings can assist local disaster organizations, planners, researchers, line agencies and local government in managing flood hazards in the area. Lastly a cumulative Flood Risk Map was produced by combining the all extents identified during the flooding events 2010-20. The cumulative Flood Risk zones are classified as High Risk Zones and Mixed Zones based on the NDWI values. Results clearly suggest that 7 out of 20 the communities in the study area are situated in the High Risk Flood Zone and whereas the remaining 13 communities lies in the Mixed Zone which could be an area with very high soil moisture due to shallow flooding.